2009
DOI: 10.1111/j.1467-9701.2008.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Econometric Analysis of Foreign Direct Investment Determinants in Russian Regions

Abstract: Using a spatial autoregressive model of cross-sectional and panel data, we study the determinants and dominant strategies of foreign direct investment (FDI) inflows into Russia before and after the 1998 financial crisis. The important determinants of FDI inflows into Russian regions since the start of transition appear to be market size, the presence of large cities and sea ports, oil and gas availability, proximity to European market, and political and legislative risks. Since 1998, it appears the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 14 publications
(45 reference statements)
2
69
2
9
Order By: Relevance
“…Lessons from the literature focusing narrowly on SEZs thus suggest that the policy has been successful only for some objectives and in particular affecting the location choice of foreign investors. This is supported by related studies that report a positive impact of locational policies or institutions on the location choice of foreign investors (Cheng and Kwan, 2000, Basile et al, 2003, Crozet et al, 2004, Ledyaeva, 2009. Despite the success of attracting foreign investors to SEZs, some authors report findings that policy-created clusters do not render the same benefits for economic development as pre-existing clusters (De Propris and Driffield, 2006).…”
Section: Are Sezs Effective According To Existing Literature?supporting
confidence: 47%
“…Lessons from the literature focusing narrowly on SEZs thus suggest that the policy has been successful only for some objectives and in particular affecting the location choice of foreign investors. This is supported by related studies that report a positive impact of locational policies or institutions on the location choice of foreign investors (Cheng and Kwan, 2000, Basile et al, 2003, Crozet et al, 2004, Ledyaeva, 2009. Despite the success of attracting foreign investors to SEZs, some authors report findings that policy-created clusters do not render the same benefits for economic development as pre-existing clusters (De Propris and Driffield, 2006).…”
Section: Are Sezs Effective According To Existing Literature?supporting
confidence: 47%
“…Evidence in favour of club convergence splitting the sample in high and low-income regions is found also in static and dynamic panel specifications by Ledyaeva and Linden (2008) in the period 1996-2004. Ledyaeva (2009) performs a spatial analysis on the factors attracting foreign direct investment (FDI) at the regional level: Her results show that the presence of big 4 See Gluschenko (2010) for a complete review cities and ports, hydrocarbons extraction, and market size are drivers of inward FDI. Ahrend (2008) performs an extreme-bound analysis in a panel of 77 regions before and after the financial crisis of 1998, i.e.…”
Section: Related Literaturementioning
confidence: 99%
“…Theoretical and empirical research on FDI determinants reflects the increasing significance of FDI for economic development at both global and national level (Ledyaeva, 2009). EBRD in its Transition Reports (2002) showed that foreign investments in transition economies facilitate growth, promote technical innovation and speed up enterprise restructuring.…”
Section: Introductionmentioning
confidence: 99%